AB0766 Initial characterisation of women with breast implants in a group of patients with systemic sclerosis referred for autologous HSCT. (12th June 2018) - Khoury, H.; Burt, R.
Abstract : Background: The causal relationship between breast implants (BI) and systemic sclerosis (SSc) is still strongly contested. Objectives: To add further input to this medical controversy, we studied the initial clinical characteristics of patients with breast implants and systemic sclerosis that are referred to our centre for autologous hematopoietic stem cell transplant. Methods: From 163 patients, with the diagnosis of systemic sclerosis (SSc), limited SSc, CREST, Morphea or scleroderma sine scleroderma, referred to our centre for autologous hematopoietic stem cell transplantation, 132 were found to be females. To identify those with breast implants (BI) or have a history of breast implants, we performed a systemic chart review for all patients. Once the patients with actual breast implant devices or have history of breast implants were identified, alive patients were contacted to check the type of their breast implants (silicone vs saline), the year of insertion, the local complications, whether they were removed or replaced and the year of removal and replacement, and the type of replacement if applicable. Clinical and biological data were collected for all patients and were compared between those who have breast implants or history if breast implants and those who do not have. Results: From 132 patients with SSc or SSc variants, thirteen had history of BI (9.8%). In 12, the breast augmentation therapy preceded the development of SSc, with median time between BI insertion and the emergence of initial symptoms of SSc of 12 years (range 7–29). The remaining patient showed acceleration of her disease after BI surgery. Surprisingly, in all 12 patients for whom we could know the type of initial implants, the prostheses were saline. When we compared the clinical characteristics of those with BI and those without. Patients with BI appeared to have higher age (mean 49.95 vs 44.42 years, p=0.012, shorter time from initial symptoms to diagnosis (mean 4.76 vs 12.24 months, p=0.0001), more frequently positive ANA (13/13 vs 89/114, p=0.06) and more frequently positive anti RNA polymerase III (7/10 vs 20/78, p=0.004). Conclusions: Our data may support the hypothesis of a possible association between BI and SSc. Furthermore, these results raise questions regarding the safety of saline breast prosthesis. Finally, our finding may indicate a possible difference in the initial characteristics of SSc patients with BI and those without. Disclosure of Interest: None declared